« Comment se comporter avec un roi chrétien » : l’ouvrage perdu d’Abū l-Ḥasan ʿAlī Ibn al-Qaṭṭān et les enjeux du cérémonial almohade - Mehdi Ghouirgate (Revue des Mondes Musulmans et de la Méditerranée)
This article re-examines a document as exceptional as it is unknown. The text summarizes a book now lost entitled "How to behave with a Christian king", found in the dictionary of Ibn ʿAbd al-Malik. It was written by the scholar Abū l-Ḥasan ʿAlī Ibn al-Qaṭṭān (d. 1231) who worked all his life for the Almohads. It is the only source that has recorded information on the conduct to be adopted by the sovereign in a ceremony in the presence of a foreign prince. We find important information on Almohad ceremonial as well as the dilemmas that must be solved for the caliph. From an ideological point of view, the caliph could not officially recognize any other power. However, unable to pursue two operations on two fronts led him to negotiate with the king of León. It is also the only document to have reported a divergence of views between the caliph and the native intellectuals of the Almohad system, the Ṭalaba. This dispute highlights tensions at the top between various servants of the State. In fact they did not have the same form of legitimacy, nor quite the same interests.